2021
DOI: 10.1242/jcs.255844
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of mitochondrial and cellular dynamics by the actin-based motor Myo19

Abstract: Myosin XIX (Myo19) is an actin-based motor that competes with adaptors of microtubule-based motors for binding to the outer mitochondrial transmembrane proteins Miro1 and Miro2 (collectively Miro, also known as RhoT1 and RhoT2, respectively). Here, we investigate which mitochondrial and cellular processes depend on the coordination of Myo19 and microtubule-based motor activities. To this end, we created Myo19-deficient HEK293T cells. Mitochondria in these cells were not properly fragmented at mitosis and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 75 publications
5
23
0
1
Order By: Relevance
“…These findings are consistent with actin assembly being implicated in reorganizing and shuffling mitochondria during mitosis and mitophagy (37,51). Some of the molecular players involved in these actin-based processes are known (52), but neither mDia2's association with mitochondria nor its role in the regulation of mitochondrial distribution and function had been described. Furthermore, we discovered that mDia2 interacts with MIRO1 and that MIRO1 is essential to sustain the pro-tumorigenic activities of skin CAFs by allowing appropriate mitochondrial distribution and metabolic functions.…”
Section: Discussionsupporting
confidence: 73%
“…These findings are consistent with actin assembly being implicated in reorganizing and shuffling mitochondria during mitosis and mitophagy (37,51). Some of the molecular players involved in these actin-based processes are known (52), but neither mDia2's association with mitochondria nor its role in the regulation of mitochondrial distribution and function had been described. Furthermore, we discovered that mDia2 interacts with MIRO1 and that MIRO1 is essential to sustain the pro-tumorigenic activities of skin CAFs by allowing appropriate mitochondrial distribution and metabolic functions.…”
Section: Discussionsupporting
confidence: 73%
“…Mitochondrial metabolism and more specifically, the relationship between OXPHOS and aerobic glycolysis plays, therefore, an important role in key cellular processes such as stemness and differentiation, but is also a defining feature during carcinogenesis. While several cytoskeletal proteins such β actin, Myosin II, or Myosin XIX have been shown to regulate mitochondrial dynamics directly (Korobova et al, 2014;Majstrowicz et al, 2021;Sato et al, 2022;Yang and Svitkina, 2019) and some of them are even present within the mitochondria (Shi et al, 2022;Xie et al, 2018), changes from OXPHOS to glycolysis are likely to require complex gene expression regulation yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Myo19 depletion leads to cytokinesis failure and multinucleation likely not due to interference with the rate of mitochondrial fission and fusion, but because of misplacing mitochondria during metaphase to anaphase transition, thus generating a physical barrier against the proper assembly of the cytokinetic machinery ( Figure 5B ; Rohn et al, 2014 ). Remarkably, Myo19 is also suggested to regulate mitochondrial dynamics specifically in mitotic cells, where its deficiency leads to impaired mitochondrial fragmentation in prometaphase despite the fact that DRP1 total protein levels are elevated, further confirming the role of Myo19 in coupling mitochondrial division to mitotic progression ( Majstrowicz et al, 2021 ). The authors suggest that no difference was observed regarding the mitotic phosphorylation status of DRP1 known to regulate its pro-fission activity, however, the presence of fused mitochondria implies that future studies should address the involvement of Myo19 or in general of actin remodeling in modulating DRP1 oligomerization, interaction with its receptors and subsequent recruitment to mitotic mitochondria.…”
Section: How Is Mitochondrial Transport Regulated During Mitosis?mentioning
confidence: 72%
“…(B) Depletion of the actin-based motor protein MYO19 leads to mitochondrial misplacement which blocks the assembly of the cytokinetic machinery and results in segregation errors ( Rohn et al, 2014 ). Moreover, MYO19 is suggested to be required for the DRP1-dependent mitotic mitochondrial fragmentation ( Majstrowicz et al, 2021 ), but whether these two pathways downstream of MYO19 could be mechanistically linked remains to be investigated. (C) Disruption of the phosphorylation cascades downstream of CDK1 and AURKA leads to the continuous mitochondrial recruitment of the motor proteins Dynein and Kinesin, respectively.…”
Section: How Is Mitochondrial Transport Regulated During Mitosis?mentioning
confidence: 99%